Tillage and mulching effects on performance of maize (Zea mays)–wheat (Triticum aestivum) cropping system under varying land slopes - SINGH, RATAN; SHARMA, A R; DHYANI, S K; DUBE, R K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted at Selakui, Dehradun during 2001–04 to study the effect of tillage (conventional and minimum) and mulching practices (no mulching and live mulching) under artificially created varying land slopes (0.5, 2.5, 4.5 and 9.5%) on soil-moisture conservation, productivity and nutrient uptake in maize (Zea mays L.)–wheat (Triticum aestivum L. emend Fiori & Paol.) cropping system. Sunnhemp (Crotalaria juncea L.) intercropped with maize gave 0.87–1.09 tonnes biomass (dry weight) and accumulated 24.8–31.4 kg N/ha at 30 days of growth when it was mulched. Biomass and N accumulation generally decreased with increasing land slope and under minimum tillage. Maize performed better on moderate slopes (2.5–4.5%) than on the relatively flat (0.5%) and highly sloping land (9.5%). However, the yield of wheat decreased linearly and significantly with increasing slope due to less conservation of soil moisture on sloping lands during the previous rainy season. Conventional tillage gave significantly higher productivity of both maize and wheat than the minimum tillage. Intercropping of maize with sunnhemp and spreading the cut biomass as mulch at 30 days (live mulching) improved soil moisture conservation at maize harvest (+1.63 to 1.94%), and yield of maize (12.0%) as well as of following wheat (13.8%) compared with the no mulching.